Citizenship and its Others
XI, 208 p.
Keywords: This edited volume analyzes citizenship through attention to its Others, revealing the partiality of citizenship's inclusion and claims to equality by defining it as legal status, political belonging and membership rights. Established and emerging scholars explore the exclusion of migrants, welfare claimants, women, children and others.